2020
DOI: 10.1371/journal.pone.0229518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adjuvant radiotherapy in elderly patients with breast cancer

Abstract: Background Radiotherapy (RT) is of critical importance in the locoregional management of early breast cancer. Although RT is routinely used following breast conserving surgery (BCS), patients may occasionally be effectively treated with BCS alone. Currently, the selection of patients undergoing BCS who do not need breast irradiation is under investigation. With the advancement of personalized medicine, there is an increasing interest in reduction of aggressive treatments especially in older women. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…The high frequency at which our older cohort underwent MRM and not BCS, when compared to the younger patients (Fig. 2 ), is likely to be also a reflection of favoritism by HCP for the use of MRM to treat older BC patients as an alternative to BCS with radiotherapy, which can be inconvenient or harmful to patients who suffer from co-morbid conditions 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The high frequency at which our older cohort underwent MRM and not BCS, when compared to the younger patients (Fig. 2 ), is likely to be also a reflection of favoritism by HCP for the use of MRM to treat older BC patients as an alternative to BCS with radiotherapy, which can be inconvenient or harmful to patients who suffer from co-morbid conditions 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no difference was found in ipsilateral breast tumor recurrence, BCSS, or overall survival between elderly patients with hormone receptor positive, node negative breast cancer who received breast conserving surgery with radiation or who received breast conserving surgery without radiation [37] . It has been reported that patients aged 70 years and older with low-risk early breast cancer breast conserving therapy can avoid breast irradiation with <3% chance of relapse [40] . Overall, these compiled studies point toward two potential views towards adjuvant radiation therapy: 1. adjuvant radiation therapy offers a potentially small benefit to prevent recurrence, but probably does not improve survival or 2. adjuvant radiation therapy offers no additional benefit when compared to other guideline adherent options.…”
Section: Discussionmentioning
confidence: 99%
“…For elderly patients, radiation therapy can be recommended based on risk stratification; as it might be safely omitted for low-risk group. 61 Older patients carry higher risk of radiation-related toxicities due to accumulative effect related to heart and respiratory comorbidities. However, recent…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…For elderly patients, radiation therapy can be recommended based on risk stratification; as it might be safely omitted for low-risk group. 61 Older patients carry higher risk of radiation-related toxicities due to accumulative effect related to heart and respiratory comorbidities. However, recent advances in radiation therapy and utilization of modern organ sparing techniques, resulted in better understanding of underlying factors that may enhance toxicities.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%